2008
DOI: 10.11646/zootaxa.1910.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, biology, and efficacy of two Australian parasitoids of the eucalyptus gall wasp, Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae: Tetrastichinae)

Abstract: Two species of Tetrastichinae (Hymenoptera: Eulophidae) from Australia are described as parasitoids of Leptocybe invasa Fisher & La Salle: Quadrastichus mendeli Kim & La Salle sp.nov. and Selitrichodes kryceri Kim & La Salle sp. nov. These parasitoids were introduced to Israel as part of a biological control program to counter the severe levels of damage caused by L. invasa to Eucalyptus plantations throughout the Mediterranean Basin. The biology of these species, as well as their potential as biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 21 publications
0
62
0
3
Order By: Relevance
“…This study provides the first report of Q. mendeli in South Africa and in sub-Saharan Africa. Quadrastichus mendeli is a parasitoid of young and mature L. invasa larvae and it is currently unknown whether the larvae are killed immediately or shortly after parasitization (Kim et al 2008). Quadrastichus mendeli is a uniparental and solitary parasitoid with an approximate developmental time of 30 days at 28.1°C (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study provides the first report of Q. mendeli in South Africa and in sub-Saharan Africa. Quadrastichus mendeli is a parasitoid of young and mature L. invasa larvae and it is currently unknown whether the larvae are killed immediately or shortly after parasitization (Kim et al 2008). Quadrastichus mendeli is a uniparental and solitary parasitoid with an approximate developmental time of 30 days at 28.1°C (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Quadrastichus mendeli is a parasitoid of young and mature L. invasa larvae and it is currently unknown whether the larvae are killed immediately or shortly after parasitization (Kim et al 2008). Quadrastichus mendeli is a uniparental and solitary parasitoid with an approximate developmental time of 30 days at 28.1°C (Kim et al 2008). Laboratory studies in Israel have shown a parasitism rate of between 7.9 and 84%, depending on the life stage attacked (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, biological control is a preferred strategy that has shown much promise. For example, the parasitic wasps, Quadrastichus mendeli Kim & La Salle (Hymenoptera: Eulophidae) and Selitrichodes kryceri Kim & La Salle (Hymenoptera: Eulophidae) have been introduced to Israel from Australia in an effort to control L. invasa in the Mediterranean region (Kim et al , 2008). An Australian Megastigmus species (Hymenoptera: Torymidae) (Doğanlar & Hassan, 2010), two Megastigmus species native to Israel and Turkey (Protasov et al , 2008) and a range of parasitoids native to India (Kulkarni et al , 2010), have also been used.…”
Section: Introductionmentioning
confidence: 99%
“…An Australian Megastigmus species (Hymenoptera: Torymidae) (Doğanlar & Hassan, 2010), two Megastigmus species native to Israel and Turkey (Protasov et al , 2008) and a range of parasitoids native to India (Kulkarni et al , 2010), have also been used. Detailed work on the biology of S. kryceri and Q. mendeli has shown parasitism levels of 52% and 73%, respectively (Kim et al , 2008).…”
Section: Introductionmentioning
confidence: 99%